2007
DOI: 10.1007/s00213-007-0711-5
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of Naltrexone and GBR 12909 on ethanol drinking-in-the-dark in C57BL/6J mice

Abstract: The DID model demonstrates predictive validity. Both opioid and dopamine signaling are involved in ethanol drinking to intoxication. Different physiological pathways mediate high ethanol drinking as compared to water or sugar water drinking in DID. DID may be a useful screening tool to find new alcoholism medications and to discover genetic and neurobiological mechanisms relevant to the human disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
111
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(124 citation statements)
references
References 54 publications
10
111
2
1
Order By: Relevance
“…In vivo the consumption of alcohol in one setting implies that the entire dose of alcohol is consumed at once, while a 'binge' is defined by NIAAA as an excessive pattern of alcohol drinking that produces BAL greater than 0.08% within a 2-h period and may, or may not, be associated with dependence [11,12,17,18] . Thus any model using consumption of biologically active amounts of alcohol within 2 h is considered an acceptable model of AAA [81,[107][108][109][110][111][112][113][114][115][116][117][118][119][120][121] . (2) Establish an exposure to an accurate concentration of ethanol.…”
Section: Models Of Aaamentioning
confidence: 99%
See 3 more Smart Citations
“…In vivo the consumption of alcohol in one setting implies that the entire dose of alcohol is consumed at once, while a 'binge' is defined by NIAAA as an excessive pattern of alcohol drinking that produces BAL greater than 0.08% within a 2-h period and may, or may not, be associated with dependence [11,12,17,18] . Thus any model using consumption of biologically active amounts of alcohol within 2 h is considered an acceptable model of AAA [81,[107][108][109][110][111][112][113][114][115][116][117][118][119][120][121] . (2) Establish an exposure to an accurate concentration of ethanol.…”
Section: Models Of Aaamentioning
confidence: 99%
“…For in vitro studies the 10-100 mmol/L ethanol range is considered physiological, with 25 mmol/L ethanol being close to 0.08% BAL achieved in vivo after 4-5 drink equivalents [7,11,12,[98][99][100][101][102][103][104][105][106] . For the in vivo studies an 0.08% BAL or above this level yields signs of intoxication and it is employed in the majority of biomedical studies [107][108][109][110][111][112][113][114][115][116][117][118][119][120][121] . (3) Recruit individuals who are currently not and never have been alcohol abusers for in vivo studies and employ alcohol-naïve primary cells or cell lines for in vitro studies.…”
Section: Models Of Aaamentioning
confidence: 99%
See 2 more Smart Citations
“…However, the DID phenotype is proving to be a useful way to explore mechanisms underlying binge-like drinking. DID was shown to be reduced by intraperitoneal naltrexone doses that did not affect water or sugar-water intake (Kamdar et al 2007). Another group has shown that the GABA B agonist baclofen reduced ethanol DID without affecting water drinking, while two GABA A agonists, THIP and muscimol, reduced drinking nonspecifically (Moore et al 2007).…”
Section: Selective Breedingmentioning
confidence: 99%